Human Resource Management and Academic Staff Productivity in Tertiary Institutions in Southwest, Nigeria - ADEDAPO, Adesina Ajayi; AJAYI, I. A. (Advances in Social Sciences Research Journal, 2021)
The study examined the relationship between human resource management and academic staff productivity in tertiary institutions in Southwest, Nigeria. The descriptive research design of the survey type was adopted in the study. The population consisted of 21,784 academic staff of the public tertiary institutions in Southwest, Nigeria. The sample for this study consisted of 1,324 academic staff selected from 12 public tertiary institutions (Federal and State) in the Southwest, Nigeria. Multi – stage sampling procedure was used in the selection of the sample for the study. The data for this study were collected through the use of two sets of self – designed questionnaire tagged “Human Resource Management Questionnaire (HRMQ)” and “Academic Staff productivity Questionnaire (ASPQ)” The instruments were subjected to screening by experts in the areas of Tests and Measurement and Educational Management. The reliability of the instruments was carried out using the test re-test method which yielded reliability coefficient of 0.80 and 0.76 for HRMQ and ASPQ respectively. The data obtained for the study were analysed using Pearson Product Moment Correlation at 0.05 level of significance. The study revealed that performance appraisal, employee relation and job design were significantly related to academic staff productivity. It was recommended among others that the job roles of each academic staff should be clearly spelt out by management of tertiary institutions. And, job performance of academic staff should be continually appraised by management of tertiary institutions through the Head of Departments. Again, the management should continue with the trend of communication flow among academic staff and between academic staff and other stakeholders in the institution to foster cordial relationship.